(3TQM ddTLQI GdfYeGfjI dGHf YQHjs - (3eLghds
(3ChdgG (B:s
... (3hNOe GdeTGjN hGdChdjGA Cgd GdTQjYI hGdMbjbjI MJi aJM Gddg Ydjg hUGQ ef Cgd GdcTb hGdTghO aTQY aj JCdja GdcJH hGdQSGFd hGSJfHGW GdCSQGQ ef GdYdhe aj cd af MJi TGY PcQg hYXe bOQg aj CbWGQ GdCQV (B...s
(3BNQgG (B:s
... (3hde jSeM GdReGf HeKd Jdc GdOGFQI dchfgG dcd GdOhGFQ bGgQI HCNHGQ GdbGgQI , hdeG CWdYfj Gddg JYGdi Ydi eG ajgG ef GdQehR GdETGQGJ CMHHJ Gf CTQMgG TQMG cGajG jMd eTcdGJgG (B...s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GdMQha hGdChaGbs